Cerebrospinal Fluid Hypovolemia and Posterior Reversible Encephalopathy Syndrome - Zheng, Yuan-yuan; Weng, Xiong-peng; Fu, Fang-wang; Cao, Yun-gang; Li, Yan; Zheng, Guo-qing; Chen, Wei (Frontiers in Neurology, 2020)
Posterior reversible encephalopathy syndrome is a reversible neuroradiological syndrome characterized by reversible vasogenic edema. The pathophysiological mechanisms are still unclear, but PRES may be triggered by various etiologies. To date, only few PRES cases linked to cerebrospinal fluid (CSF) hypovolemia were reported. The association between PRES and CSF hypovolemia need to be explored. We presented a case of PRES with CSF hypovolemia as a result of an inadvertent dural puncture and reviewed the literature to identify the clinical characterization and pathophysiological mechanism of PRES following CSF hypovolemia. A total of 31 cases of PRES-CSF hypovolemia was included for analysis. The medium age was 33 years, with a notable female predominance (87.1%). Fifteen patients (48.4%) didn’t had either a history of hypertension nor episode of hypertension. The most common cause of CSF hypovolemia was epidural or lumbar puncture (n=21), followed by CSF shunt (n=6). The median interval between the procedure leading to CSF hypovolemia and PRES was four days. Seizure, altered mental state and headache were the most frequent presenting symptom. The parieto-occipital pattern was most frequent (71.0%). Conservative management remains the mainstay of treatment with excellent outcome. Three patients had a second episode of PRES. CSF hypovolemia is a plausible cause of PRES via a unique pathophysiologic mechanism including arterial hyperperfusion and venous dysfunction. Patients with CSF hypovolemia is more susceptible to PRES, which is potentially life-threatening. Given that CSF hypovolemia is a common complication of anesthetic, neurological, and neurosurgical procedures, PRES should be early considered for prompt diagnosis and appropriate management.